Sistem Informasi Repository Berbasis Web Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Palembang Dengan Menggunakan Framework Codeigniter - Muhammad syahril; Muhammad Andryansyah (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
The Repository Information System Is Implemented In Order To Create The Needs Needed By The Faculty Of Teacher Training And Education. Therefore, the Repository Information System must be implemented by the Faculty of Teacher Training and Education to support accreditation to become a high-impacted faculty.The purpose of this research is to help one of the governance systems in the teaching and education faculties, especially in the field of scientific writing or libraries, the author creates a WEB-based Repository Information System for the Teaching and Education Faculty, University of Muhammadiyah Palembang using the Codeigniter Framework (PHP).The Data Collection Method Is Observation, Literature Study To Determine What Is Needed In Making The Repository Information System. Keywords: Repository, Scientific Writing, Library, Faculty of Teacher Training and Education, University of Muhammadiyah Palembang